The efficacy of explicit articulatory phonetics instruction in L2 pronunciation acquisition: A systematic review of pedagogical approaches for Spanish L1 Learners of English: La eficacia de la instrucción fonética articulatoria explícita en la adquisición de la pronunciación L2: Una revisión sistemática de los enfoques pedagógicos para estudiantes de español L1 que hablan inglés - Pacheco Vasquez , Edwin Alexander; Veas Aguirre , Shirley Jamileth (Boletín Científico Ideas y Voces, 2025)
This systematic literature review examines the efficacy of explicit articulatory phonetics instruction in improving pronunciation accuracy among Spanish L1 learners of English as a second language. Through analysis of 15 empirical studies published between 2020-2025, this review investigates how explicit instruction in manners and places of articulation affects production of challenging English phonemes, particularly interdental fricatives and vowel contrasts. The findings indicate that explicit phonetics instruction consistently outperforms traditional implicit approaches in improving segmental accuracy and comprehensibility. Key effective strategies identified include tactile feedback mechanisms, high-variability phonetic training, and visual articulation tools. However, the review also reveals significant gaps in current research, including limited longitudinal studies and insufficient investigation of transfer to spontaneous speech. The analysis suggests that while explicit articulatory instruction shows strong promise, its effectiveness is moderated by factors such as learner proficiency, instructional duration, and target phoneme complexity. These findings have important implications for curriculum design and pedagogical practices in second language pronunciation teaching